Noncanonical inflammasomes: Antimicrobial defense that does not play by the rules. (15th February 2017) - Crowley, Shauna M.; Vallance, Bruce A.; Knodler, Leigh A.
Abstract: Although much research has focused on defining the actions of caspase‐1 containing canonical inflammasomes in promoting host defense, noncanonical inflammasomes have received comparatively little attention. Exciting new concepts have recently emerged detailing their atypical mechanism of activation, importance in defending against cytosolic Gram‐negative pathogens, and role in innate immune defenses of nonmyeloid cells, which has revamped interest in the study of noncanonical inflammmasomes. Here, we will discuss these latest findings about caspase‐4, ‐5, and ‐11 containing inflammasomes in the context of their role in pathogen elimination in mice and humans.